Dry matter losses and quality changes during short rotation coppice willow storage in chip or rod form. (May 2018) - Whittaker, Carly; Yates, Nicola E.; Powers, Stephen J.; Misselbrook, Tom; Shield, Ian
Abstract: This study compares dry matter losses and quality changes during the storage of SRC willow as chips and as rods. A wood chip stack consisting of approximately 74 tonnes of fresh biomass, or 31 tonnes dry matter (DM) was built after harvesting in the spring. Three weeks later, four smaller stacks of rods with an average weight of 0.8 tonnes, or 0.4 tonnes DM were built. During the course of the experiment temperature recorders placed in the stacks found that the wood chip pile reached 60 °C within 10 days of construction, but the piles of rods remained mostly at ambient temperatures. Dry matter losses were calculated by using pre-weighed independent samples within the stacks and by weighing the whole stack before and after storage. After 6 months the wood chip stack showed a DM loss of between 19.8 and 22.6%, and mean losses of 23.1% were measured from the 17 independent samples. In comparison, the rod stacks showed an average stack DM loss of between 0 and 9%, and between 1.4% and 10.6% loss from the independent samples. Analysis of the stored material suggests that storing willow in small piles of rods produces a higher quality fuel in terms of lower moisture and ash content; however, it has a higher fine content compared to storage in chip form. Therefore, according to the two storage methods tested here, there may be a compromise between maximising the net dry matter yield from SRC willow and the final fine content of the fuel. Highlights: Willow cut as wood chips and rods were stored in stacks for 6 months. The wood chip stack lost 18.9–23.5% of the DM compared to 0–9% lost in the rods. Storing willow as rods produces a lower moisture and ash content fuel. Chipped rods have a higher fine content compared to stored chips.